Maternal body mass index and feto-maternal outcome: a comparative study - Hemalatha, N.; ., Shanthini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Increasing BMI in women poses multiple threat of illness especially in the reproductive age group impacting pregnancy. Pregnant women with overweight and obesity are at a higher risk of developing complications at all stages of the physiological pregnancy. A focus on the methods to prevent this trend of increasing weight gain in adolescence is essential curb the complications due to obesity. Methods: This prospective study was conducted in the Department of Obstetrics and Gynecology, Madras Medical College, Chennai. Written informed consent was obtained and pregnant women visiting the antenatal OP were registered. Detailed history taking and examination was carried out with the measurement of body mass index as weight in kg/height in meter square. The women were followed up for the antepartum, intrapartum, post-partum variables and neonatal outcome. Results: Two hundred pregnant women with high BMI >25 kg/m2 and two hundred pregnant women with normal BMI were selected and were followed prospectively. Present study showed an increased incidence of pre-eclampsia in patients with high BMI (28% as compared to 8% of the normal BMI) and a higher incidence of Gestational diabetes mellitus among women with high BMI with a value of 27.5 % compared to a value of 7.5% in women with normal BMI. Caesarean delivery was found in 54.5% of the high BMI mothers compared to 31.5% in normal BMI mothers. Postoperatively, wound gaping was found with an incidence of 4.5% in high BMI mothers. IUGR was found in 10% of babies of women with high BMI and still birth occurred in 2.5% of deliveries of high BMI mothers compared to 0.5% in mothers of normal BMI group. Conclusions: The obstetrician needs to be well versed with dietary advice and life style pattern advice to the women of the reproductive age group in order to prevent the complications of high Body mass index in pregnancy. Its imperative to counsel these women about the pre-pregnancy loss of weight, healthy food and exercise, and healthy life style pattern during pregnancy in order to have a healthy outcome.